Islam dan Pancasila: Pergulatan Islam dan Negara Periode Kebijakan Asas Tunggal - Humaidi, Zuhri (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This article discusses the Muslims characterization and response mapping toward Pancasila as mono ideology that was implemented in the years of 1980 and around. For that reason, Islam moderate had studied that was represented by Masyumi exponents and some groups that were identified as moderate organization and traditional Islam response that was represented by NU. So far, study and research have been conducted in that case or Islamic politics in a whole, focused on the response from moderate Islam, This is caused by the assumption that moderate Islam indicated as a pioneer and a good place to the growing of modernization and reformation, as the representation of flexibility and development. This fact is in contradiction with the assumption that engaged with traditional Islam that has been stereotyped as a backwardness representation. This article is trying to analyze that assumption.